2019
DOI: 10.2147/ppa.s182516
|View full text |Cite
|
Sign up to set email alerts
|

<p>A qualitative study on the design and development of an mHealth app to facilitate communication with the Deaf community: perspective of community pharmacists</p>

Abstract: PurposeThis study prepares the groundwork on the potential design and development of a mobile health (mHealth) app that will be able to bridge the communication gap between pharmacists and patients who are Deaf and Hard of Hearing (DHoH).Patients and methodsA focus group discussion was conducted with 12 community pharmacists. Participants were recruited using snowball sampling. Audio-recordings were transcribed verbatim, and analyzed using a thematic approach.ResultsThree themes were apparent: 1) suggestions f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 31 publications
0
16
0
2
Order By: Relevance
“…It enables health care providers and organizations to offer information and services to patients and caregivers through digital tools . The development of complex automated systems to generate, store, share, and disseminate health‐related information to different stakeholders has augmented interpersonal health communication . Mobile‐based systems are also being used to track health behaviors and collect health data with less effort and cost .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It enables health care providers and organizations to offer information and services to patients and caregivers through digital tools . The development of complex automated systems to generate, store, share, and disseminate health‐related information to different stakeholders has augmented interpersonal health communication . Mobile‐based systems are also being used to track health behaviors and collect health data with less effort and cost .…”
Section: Introductionmentioning
confidence: 99%
“…In many such ways, digital health technologies are changing the way people interact in the modern health care ecosystem . Several studies have shown health benefits following the adoption of digital communication in health care, including effective and efficient management of health conditions, shared decision making, improved care for chronic diseases, and better relationship among the patients and providers . On the other hand, the use of digital technologies in health has also introduced new challenges including privacy concerns, diminished in‐person face‐to‐face communication, limited digital health literacy in underserved populations, persistent digital divide, and public trust issues…”
Section: Introductionmentioning
confidence: 99%
“… 58 Malaysian DHOH individuals have also expressed that pharmacists should attend sign language training which would help them learn about Deaf culture. 35 Solutions to providing accessible healthcare to DHOH patients should not only be limited to ensuring accessible communication in sign language but also, extended towards providing culturally sensitive Deaf services.…”
Section: Discussionmentioning
confidence: 99%
“… 34 This was further supported in another Malaysian study where community pharmacists found it challenging to communicate with DHOH patients which may have been attributed to their lack of knowledge on the sociocultural aspect of deafness. 35 To date, the cultural competency movement in Malaysia’s pharmacy education has been slow in uptake. This may be owed to the lack of established accreditation standards addressing cultural competency in pharmacy programmes and the absence of guidelines on cultural competency from the Ministry of Health.…”
Section: Introductionmentioning
confidence: 99%
“…Access to health care for Deaf and Hard of Hearing (D&HH) patients has proven to be a global challenge [5][6][7][8]. A study conducted among 91 Deaf individuals and their experiences with using American Sign Language (ASL) in the healthcare environment found that D&HH individuals were afraid of miscommunication with their physician and preferred the use of an interpreter [9]. According to a systematic review of specialized healthcare for D&HH people, hospitals and health care systems in 30 countries had access to a quali ed sign language interpreter; however, the availability of those interpreter services was still limited [6,8,10].…”
Section: Introductionmentioning
confidence: 99%